ANALISIS PIUTANG PADA PT. NUANSA DHARMA CIPTA DI SAMARINDA - rina, widya Astuti (EKONOMIA, 2018)
This study aims to analyze the turnover rate of receivables at PT. Nuansa Dharma Cipta in the period 2013 - 2017. As a business unit that in its activity always aim to earn profit then it is proper PT. Nuansa Dharma Cipta perform strategies to improve the company's ability to generate profits by making sales on credit. From the data obtained from the company can be analyzed using a special ratio analysis related to Receivable Turnover Rate, Receivable Collection Period, Delinquency Ratios and Billing Ratios.The results of this study show that the Turnover Rate of Receivables PT. Nuansa Dharma Cipta 2013 by 39.10 times, in 2014 42.68 times, in 2015 has increased ie, 59.34 times, 2016 40.64 times and in 2017 there is a 43.76 times a year. The period of collection of receivables in 2013 may accumulate 9 days, 2014 8 days, 2015 6 days, 2016 9 days and 2017 8 days. The ratio of arrears fluctuated which in 2013 by 9.7%, in 2014 by 13, by 2015 by 8.9%, by 2016 by 7.5% and by 2017 by 8.2%. The billing ratio has fluctuated in 2013 by 90.3%, by 2014 by 87%, by 2015 by 91%, by 2016 by92.5% and by 2017 by 91.8%. Based on the results of the research receivables turnover fluctuations occur every year but tend to increase. The calculation result of the collection period of accounts receivable fluctuated but the collection period of receivables is less than 30 days, so it can be said the company is able to make billing in a timely manner. The calculation of the ratio of arrears in 2014 occurred shocks due to the large ratio of arrears from the previous year. The calculation of the billing ratio fluctuates but in 2016 the most prominent increase from the previous year